"What on Earth Is Smenkhkare?" WH‐Questions, Truth‐Makers, and Causal‐Informational Account of Reference. Issue 2 (3rd November 2021) - Sinokki, Jani
Abstract: Although the historical‐causal picture of reference Kripke sketches in Naming and Necessity is highly influential, Kripke in fact says very little about what reference is and how it comes about. In this paper I point out that the possibility of asking WH‐questions (i.e. 'what?', 'who?', 'which?') about a sound or inscription pattern (e.g., what does that refer to?) shows that in case of names especially, their reference, if there is one, will be preserved by a causal‐historical chain constituted by transmissions of the (physical) patterns themselves, even in absence of language users or any linguistic intentions. I sketch out a causal‐informational theory of reference, that holds that the causal aspect of refence transmission is due to two‐factors. On the other hand there are informational chains constituted by data transmissions, on the other, also communicational rules by which speakers can interpret the data as information of something are needed. In most part the causal‐informational theory sketched in the paper can be viewed as complementing Kripke's original causal picture. However, I will argue that Kripke's account of fixing the reference of proper names in 'initial baptisms' is inadequate. I will argue that most cases of seemingly fixing the reference via use of a definite description (e.g., the naming of Neptune) in fact presuppose a prior causal‐informational connection to the named object, thus essentially fixing the reference in the same way as in cases of baptism by ostension. I will further argue that in the cases that do not fall into the previous category, the baptism by definite description simply fail to fix any reference. I thus conclude that there is no such thing as fixing the reference of a proper name by definite description.